Developing of MITRA learning model of problem solving-based to solve mathematical problems in elementary school - Rika Damayanti; Mawardi Mawardi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
The research aimed to develop the steps of MITRA learning model of problem solving-based to solve mathematical problems in elementary school, to know the product’s validity level of MITRA learning model of problem solving-based according to expert’s validation, and to assure the effective level of MITRA learning model of problem solving-based. The research type was Research and Development (RD), which is a procedure to develop a new product or improve the existed product. The research procedure was divided into three stages, they are: preliminary study, developing model stage, and testing product. The research results found: (1) the steps of MITRA learning model of problem solving-based are: problems identification, implementation of MITRA, and evaluation of MITRA; (2) product’s validity level of MITRA learning model of problem solving-based according to expert’s validation was 3,75 (75%) on high category, and the media expert was 214 (76,5%) on high category; and (3) product’s effectiveness was on very effective category for students of grade 4 elementary school reaching 97%, and the result was significantly higher than pretest (60%).